Cardiopulmonary effects of apneustic anesthesia ventilation in anesthetized pigs: a new mode of ventilation for anesthetized veterinary species - Bukoski, Alex; Downs, John; Hodgson, David S.; Le-Bert, Carolina R.; Thomen, Robert; Flors, Lucia; Thombs, Lori; Bailey, James (Frontiers in Veterinary Science, 2024)
Objective To compare the cardiopulmonary effects of apneustic anesthesia ventilation (AAV) and conventional mechanical ventilation (CMV) in anesthetized pigs and to describe a new mode of ventilation for anesthetized veterinary species. Study design Randomized, crossover design without washout. Animals Twelve healthy, female white Landrace pigs. Methods Following ketamine-midazolam premedication and anesthetic induction with propofol, the trachea was intubated, and each pig was positioned in dorsal recumbency. Anesthesia was maintained with propofol and sufentanil infusions. Pigs were instrumented and their lungs were sequentially ventilated with each mode, in random order, for 1 h according to predefined criteria [fraction of inspired oxygen (FiO2) = 0.21, 10 mL kg−1 tidal volume (VT), and arterial carbon dioxide tension (PaCO2) within 40–45 mmHg]. Cardiopulmonary data were collected at baseline, 30 and 60 min. In 8 pigs, thoracic computed tomography (CT) was performed following the 60 min time point for each mode of ventilation and images were analyzed to quantify lung aeration. The effects of ventilation mode, time, and order were analyzed using repeated measures ANOVA. Paired t-tests were used to compare lung aeration between modes. Significance was defined as p < 0.05. Results Data from 12 pigs were analyzed. A significant effect of mode was found for heart rate, mean arterial pressure (MAP), pulmonary artery occlusion pressure, cardiac index (CI), stroke volume index, systemic vascular resistance, pulmonary vascular resistance, oxygen delivery index (DO2I), oxygen extraction ratio (O2ER), VT, arterial oxygen tension, arterial hemoglobin saturation, PaCO2, end-tidal carbon dioxide tension, alveolar dead space (VDalv/VTalv), venous admixture (Q.s/Q.t), mean airway pressure, and dynamic compliance index (CRSI). Order effects were also observed for some cardiovascular and respiratory variables. For the eight pigs that underwent thoracic CT, AAV resulted in significantly larger proportions of normally and hyperaerated lung while CMV resulted in larger proportions of hypoaerated and atelectatic lung. Conclusions In dorsally recumbent anesthetized pigs, ventilated with FiO2 = 0.21, both modes of ventilation supported adequate oxygenation while AAV resulted in higher CRSI, and lower VDalv/VTalv and Q.s/Q.t, compared with CMV. AAV was also associated with lower MAP, CI, and DO2I and higher O2ER compared with CMV. Further investigation of AAV in anesthetized animals is warranted.